Is it possible to diagnose lymphoproliferative lesions by fine needle aspiration biopsy? - Chosia, Maria; Wolska-Szmidt, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Despite the fact that fine needle aspiration biopsy (FNAB) is a commonly employed method in modern oncological diagnostic management, it has found no extensive use to diagnose lymphoproliferative lesions of the orbit and eye adnexa. Benign and malignant lymphoproliferative lesions and pseudotumor have a very similar clinical course. Microscopicaly, the lesions are also similar and hence even on histology it is difficult to differentiate between these conditions based on the morphology. We believed, that routine cytology and flow cytometry and/or PCR method in materials obtained in the course of FNAB are fast and sensitive methods and in many cases allow to avoid a surgical biopsy.